The effect of exchange rates and interest rates on Indonesia's international trade performance during 2015–2024 - Artha Putri Br Karo; Debora Silvia Hutagalung; Septri Anisa; Andreas Panjaitan (Economic: Journal Economic and Business, 2026)
The purpose of this study is to examine the relationship between exchange rates and interest rates on a country's foreign trade performance. Exchange rate movements influence the price competitiveness of exported and imported goods, while changes in interest rates impact capital flows and the stability of the national currency. This study applies quantitative methods using secondary data obtained from Indonesian government financial reports, international trade statistics, and monetary indicators for the period 2015 to 2024. The analysis shows that exchange rate depreciation generally encourages exports but suppresses imports. Meanwhile, interest rate increases have varying impacts, depending on market responses, particularly from investors and domestic consumers. Therefore, exchange rate stability and the implementation of appropriate interest rate policies are strategic factors in supporting the performance of the international trade sector.